Efektivitas Tata Kelola Surat-Menyurat dan Arsip dalam Menunjang Kinerja Organisasi Perangkat Daerah di Dinas Sosial Kota Surabaya. - Elysia Irma Fransiska; Bambang Kusbandrijo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Archives play an important role in supporting the effectiveness of organizational administration, particularly within government institutions. This study aims to examine the management of correspondence and archives at the Surabaya Social Service Office. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that correspondence management has been carried out through several stages, including receipt, recording, disposition, and distribution of letters. Archive management is conducted through the classification, storage, and maintenance of documents to ensure easy retrieval when needed. Although the management of correspondence and archives has generally been implemented effectively, several challenges remain, including document accumulation, limited human resources with archival expertise, and the suboptimal implementation of archive digitization. Therefore, efforts are needed to improve staff competencies, provide adequate facilities and infrastructure, and implement a digital archiving system to enhance administrative effectiveness at the Surabaya Social Service Office.